Stability of Tranexamic Acid after 12-Week Storage at Temperatures from –20°C to 50°C. (1st July 2013) - de Guzman, Rodolfo; Polykratis, I. Amy; Sondeen, Jill L.; Darlington, Daniel N.; Cap, Andrew P.; Dubick, Michael A.
Abstract Background. Tranexamic acid (TXA) is an antifibrinolytic agent that reduces blood loss during surgery, decreases mortality in civilian and military trauma populations, was adopted for prehospital use by the British military, and is now issued to U.S. Special Operations Forces for use on the battlefield. Objective. This study tested whether storage of TXA ampoules at four temperatures (–20°C, 4°C, 22°C, or 50°C) for 1, 2, 4, and 12 weeks would result in chemical degradation and the loss of activity to block streptokinase-induced fibrinolysis in human plasma. Methods. For each temperature and storage duration, normal plasma, plasma plus streptokinase (SK) (50 units/mL), and plasma + SK + TXA (0.2 μg/mL, n = 4) were tested for D-dimer (DD), for fibrin degradation products (FDP), by thromboelastography (to measure the units/mL of SK needed to get 100% fibrinolysis at 60 minutes [LY60]), and by high-performance liquid chromatography (HPLC). The results were similar for all temperatures and storage durations, and were therefore combined. Results. Streptokinase led to a rise in LY60, DD, and FDP that was significantly (p < 0.05) attenuated with TXA. The results in the three test conditions were LY60: 0.00% ± 0.00%, 70.52% ± 4.7%, 0.02% ± 0.01%; DD: 0.23 ± 0.1, 205.05 ± 101.59, 0.31 ± 0.01 mg/L; and FDP: <10, >40, and <10 μg/mL, respectively. The HPLC results showed no chemical breakdown of TXA. All TXA glass ampoules at –20°C were cracked by week 1. Conclusions. Except for the finding that TXA ampoules cracked when frozen, this study indicated that the drug remains effective when stored under conditions likely to be encountered in the prehospital environment and outside the manufacturer's recommended temperature range for at least 12 weeks.